A Critical Archival Pedagogy: The Lesbian Herstory Archives and a Course in Radical Lesbian Thought - Carden, Kailah R.; Vaught, Sabina E.; Muñoz, Arturo; Pinto, Vanessa; Vaught, Cecilia; Zeigler, Maya (Radical Teacher, 2016)
This paper is the story of a critical archival pedagogy that emerged through the undergraduate course Radical Lesbian Thought. As teachers and students, we dialogically co-constructed the praxis and content of the course throughout the semester. We employed archives throughout the course as theory, site, and pedagogy. In this paper we identify three archival frameworks: dialogue and difference, collaborative knowledge production, and archival methodology; and detail how they informed three course activities: reading and writing archival letters, visiting the Lesbian Herstory Archives, and completing final archival projects. We argue that archives provide theoretical and practical opportunities, in the tradition of critical pedagogy, to challenge and rearrange powered classroom structures and practices of thought.